Laser self-induced tunable birefringence of magnetic fluid - Chan, Chi Chiu (2013)
The phenomenon of laser self-induced tunable birefringence of magnetic fluid is investigated. This phenomenon exists in magnetic fluid, no matter whether it is under an external magnetic field or not. The variation trend of the laser self-induced birefringence with the laser power follows a linear relationship. Besides, dichroism is not observed in accompany with the laser self-induced birefringence.